Keping Puzzle Yang Hilang: Menelaah Hak Yang Sirna Terhadap Narapidana - Azis, Muhammad Abdul; Putri, Riski Ananda Kusuma; Rahman, Nur (UI Scholars Hub, 2022)
Prisons have a reputation for being cages of deprivation of freedom and atonement for wrongdoing. Prisoners lose their independence because prisons restrict their movement, including their sexual needs, which is like the